VIABILITAS BENIH NYAMPLUNG (Calophyllum inophyllum L) DARI BIJI YANG TELAH DI SKARIFIKASI TERHADAP MEDIA TANAM YANG BERBEDA - Noor Khamidah; Arief Rakhmad Budi Darmawan (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2018)
Nyamplung (Calophyllum inophyllum L) is one of the non edible oils and potentially as an alternative energy source, biodiesel. The superiority of biodiesel from nyamplung seeds is 40-73% oil yield. In Indonesia, Nyamplung is widespread from the islands of Java, Kalimantan, Sulawesi, Sumatra and Papua. Good plant propagation techniques are needed to improve crop productivity.This study aims to determine the viability of Nyamplung seeds from seeds that have been scarification to different planting media, to know the best planting media in the cultivation process Nyamplung. The implementation of the research was carried out on the land in Banjarbaru Selatan, South Kalimantan using Completely Randomized Design (RAL). The experimental design consists of a mixture of different compositions of different planting media, ie soil (control), soil and husk, soil and bokashi fertilizer, soil + husk + bokashi fertilizer. The results showed that the viability of Nyamplung seed was influenced by the planting medium. The best seededness of Nyamplung seeds was obtained in the combination of planting media in the form of soil mixture + husk + bokashi, which was significantly different from other treatments on plant height variables, while for leaf number variables showed no significant difference between planting media treatment used in the study.